A validation of the Japanese adaptation of the Big Five Inventory-2 - Yoshino, Shinya; Shimotsukasa, Tadahiro; Oshio, Atsushi; Hashimoto, Yasuhiro; Ueno, Yuki; Mieda, Takahiro; Migiwa, Ifu; Sato, Tatsuya; Kawamoto, Shizuka; Soto, Christopher J.; John, Oliver P. (Frontiers in Psychology, 2022)
The purpose of this study was to adapt a Japanese version of the Big Five Inventory-2 (BFI-2-J) to examine its factor structure, reliability, validity, and measurement invariance. The BFI-2-J assesses five domains and 15 facets of the Big Five personality traits. We analyzed two datasets: 487 Japanese undergraduates and 500 Japanese adults. The results of the principal component analysis and confirmatory factor analysis revealed that the domain-facet structure of the BFI-2-J was similar to that of other language versions. The reliability of the BFI-2-J is sufficient. The correlation coefficients between the BFI-2-J and the other Big Five and self-esteem measures supported convergent and discriminant validity. Moreover, we confirmed measurement invariance across age and sex groups in domain-level and facet-level models. The results suggest that the BFI-2-J is a good instrument for measuring the Big Five personality traits and their facets in Japan. The BFI-2-J is expected to be useful in Japanese personality research and international comparative research.